PERTIMBANGAN HAKIM ATAS GUGATAN PENGGUGAT TIDAK DAPAT DITERIMA DALAM PERKARA PERCERAIAN - Ndruru, Antonius; Laia, Laka Dodo (LPPM Universitas Nias Raya, 2024)
Divorce is a manifestation of the failure of the goal of marriage to form a happy and eternal family. One of the divorce lawsuits that has been decided by the district court and has permanent legal force is decision number 41/Pdt.G/2021/PN Gst. In this decision, the judge handed down the decision